2003
DOI: 10.1046/j.1439-0531.2003.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ram Introduction After the Second Prostaglandin F2α Injection on Day 11 on the LH Surge Characteristics in Fat‐Tailed Ewes

Abstract: The aim of this study was to evaluate the effects of ram introduction after the second prostaglandin F2alpha (PG F2alpha) injection on day 11 on the secretion characteristics of pre-ovulatory LH surge of fat-tailed ewes. Multiparous Morkaraman ewes (n=12) were divided into three groups by balancing the groups for liveweight (BW) and body condition score (BCS). On the day of second PGF2 alpha injection (0 h), performance tested rams (n=2) were either introduced to the ewes at 0 h (ram 0 group, n=4) or at 18 h (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…It has been reported that BCS is positively correlated to timing of LH surge in sheep (Yildiz et al 2002b) and LH pulse frequencies in sheep (Robinson 1990) and cattle (Yildiz et al 1997). The link between BCS and hypothalamus, where GnRH secretion is initiated, appear to include leptin secretion from the adipose tissue (Blache et al 2000;Yildiz et al 2001) since leptin informs the hypothalamus about the sufficiency of energy stores for the initiation of reproductive activity (Blache et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that BCS is positively correlated to timing of LH surge in sheep (Yildiz et al 2002b) and LH pulse frequencies in sheep (Robinson 1990) and cattle (Yildiz et al 1997). The link between BCS and hypothalamus, where GnRH secretion is initiated, appear to include leptin secretion from the adipose tissue (Blache et al 2000;Yildiz et al 2001) since leptin informs the hypothalamus about the sufficiency of energy stores for the initiation of reproductive activity (Blache et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive competitive enzyme immunoassay method developed by Mutayoba et al (1990) for bovine LH and modified by Yildiz et al (2002b) was used to analyse LH concentrations. Briefly, D-Biotinyl-ε-aminocaproic acid N-hydroxy-succimidine ester (Biotin-X-NHS, SIGMA, Germany) was used for labelling oLH (NIDDK-oLH-I-4 (AFP-8614B)).…”
Section: Enzyme Immunoassay Of Lh Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The attempted methods are control of daily length and/ o r h o r m o n a l t r e a t m e n t s s u c h a s n a t u r a l p r o g e st e r o n e , s y n t h e t i c p r o g e s t o g e n s , prostaglandin F2α (PGF2α) or gonadotrophin releasing hormone (GnRH), and isolated ram introduction [3]. Recently, a method using PGF2α combined with GnRH was reported in ewes with a successful lambing rate after natural mating or artificial insemination [1,4]. Treatment with GnRH and PGF 2α is a practical method for controlling ovarian follicular and luteal functions and for increasing the precision of estrus synchronization in cyclic and acyclic postpartum cows and heifers [5][6][7][8].…”
mentioning
confidence: 99%
“…This may be due to the observed depletion of body reserves (Table 2) and weight loss (Figure 3), because of the low nutritional value of the herbage, which could have interrupted the sexual activity. The body condition score is positively related with the presence of a peak and pulsatile behavior of the luteinizing hormone in sheep (YILDIZ et al, 2003). Viñoles (2003) concluded that a satisfactory body score condition increased the ovulation rate in sheep, and that nutritional supplementation from day 8 to 14 of the estrus cycle increased that of sheep with moderate body score condition.…”
Section: Evaluationsmentioning
confidence: 99%